Endothelial and platelet microparticles in patients with antiphospholipid antibodies. Issue 2 (February 2015) - Breen, K.A.; Sanchez, K.; Kirkman, N.; Seed, P.T.; Parmar, K.; Moore, G.W.; Hunt, B.J.
Abstract Background The antiphospholipid syndrome (APS) is the association of thrombosis and recurrent pregnancy loss and/or pregnancy morbidity with persistent antiphospholipid antibodies (aPL). Previous studies of microparticles in patients with APS/aPL have mainly been small and findings, contradictory. Objectives To quantify endothelial and platelet microparticle levels in patients with isolated antiphospholipid antibodies or primary antiphospholipid syndrome (PAPS). Patients/Methods We measured endothelial and platelet microparticle levels by flow cytometry in 66 aPL/PAPS patients and 18 healthy controls. Results Levels of circulating platelet (CD41 and CD61) and endothelial microparticles (CD51 and CD105) were significantly increased in patients with PAPS and aPL compared to healthy controls. There were correlations between platelet and endothelial microparticles levels in all patients with aPL. Conclusions Platelet and endothelial microparticles are increased in all patient groups within this cohort of patients aPL. Whether they may have a role in the pathogenesis of APS merits further study.